Signs, Built Environments, and the Communication of Place: The Lower Wisconsin State Riverway - Spaier, Ben; Schaad, Genevieve; Gunddacker, Rachel; Gadbois, Jon (My University, 2009)
The authors of this paper employed their backgrounds in Human Geography to examine a theoretical aspect of the Lower Wisconsin Riverway with regards to signage, built environment and the perception of space and place. Our aim for this paper is to examine how humans have demarcated the Lower Wisconsin Riverway as ecologically protected and significant through signage and the built environment. The principal impetus which prompted this choice of topic stemmed from the book Space and Place: The Perspective of Experience, written by the immensely influential geographer Yi-Fu Tuan. His work explores the experience of place and how it is created by the lived, personal experiences of everyday life. We therefore chose to focus primarily on signs and maps that attempt to denote the Riverway as a place of importance that is worth protecting because they are aspects of the landscape that are mostly unchanging and are viewed daily by residents and visitors alike. The signage created by both the Lower Wisconsin Riverway Board and the Wisconsin Department of Natural Resources are clearly the most authoritative examples of place-making found along the Riverway. Throughout this project we hope to show the successes and failures of these organizations' attempts to portray the region as a "quasi-protected scenic area."
Includes color photographs, maps.
Keywords: Space and Place; Signage; Built Environment; Lower Wisconsin Riverway